THE ROLE OF THE QUALITY OF BANKING GOVERNANCE ON THE DISCLOSURE OF THE MANAGEMENT COMMENTS REPORT IN ACCORDANCE WITH INTERNATIONAL AND LOCAL REQUIREMENTS - H. RASHEED, RAGHAD; E.YAGUOB, EBTEHAJ (International Journal of Psychosocial Rehabilitation, 2021)
The study aims to know the role in the application and commitment of some internationaindicators of institutional governance and mechanisms issued by the Central Bank of Iraq toenhance and increase disclosure in the report of management comments issued by economicunits. To achieve the purpose of the study, a number of Iraqi banks listed in the Iraq StockExchange were selected (Al Ahli Bank of Iraq, Iraqi Trade Bank, Gulf Commercial Bank,Middle East Investment Bank, Mosul Bank for Development and Investment, Al-MansourBank for Investment, Baghdad's Al-Ahli Bank, Sumer Commercial Bank, Trans IraqInvestment Bank) as a research sample. The study relied on the analytical descriptiveapproach and designed a checklist to collect data. The data was obtained from the annualreports of the banks and for the period from (2016) to (2019), which are available in theIraqi Stock Exchange and the official websites of the banks of the study sample. It also reliedon the Corporate Governance Guide issued by the Central Bank of Iraq for the year 2018, inaddition to the (GMI) index issued by the American company (Governance MetricsInternational), in addition to its reliance on the Administrative Comments Index (Ma.Co.I)issued by the International Accounting Standards Board (IASB) year 2020. The studyreached a number of conclusions, including the existence of a discrepancy in the commitmentof the study sample banks to the mechanisms of quality governance. In addition to thediscrepancy in the disclosure of the information included in the reports of the managementcomments by the banks of the research sample